The families carditidae and condylocardiidae in the magellan and Perú-Chile provinces (bivalvia: Carditoidea) - Güller, Marina (2013)
Based on the study of available types and extant collections, this paper provides a systematic revision of the living species of Carditoidea occurring in the Magellan and Perú-Chile Provinces. Out of the 19 nominal species reported for the area, eight species are recognized as valid: Cyclocardia compressa, C. spurca, C. thouarsii, C. velutina, Carditella naviformis,C. semen, C. tegulata and Carditopsis flabellum. Other eight nominal species are regarded as synonyms: Cardita magellanica of Cyclocardia velutina; Carditella pallida of C. tegulata; Cardita australis and Actinobolus philippi of Carditella naviformis; Cardium pygmaeum of Carditella semen; Cardita paeteliana of Cyclocardia spurca; Carditella pallida duodecimcostata of Carditopsis flabellum; and Cardita congelascens of Cyclocardia thouarsii. Furthermore, Cardita malvinae and Cardium parvulum are nomina dubia, and the occurrence of Carditella exulata in Magellanic waters is doubtful.